Assessment of enhanced biodegradation potentials of animal wastes on diesel-contaminated soil - Tosan AKIRI-OBAROAKPO; Emmanuel IMARHIAGBE; Frederick EKHAISE (Studia Universitatis Babeș-Bolyai. Biologia)
Oil spillage is a menace, crippling most oil-producing regions around the globe. The aim of this study was to access the role of poultry litter and cow dung in enhancing biodegradation of diesel-contaminated soil. The treatment sets were split into three levels of diesel pollution (50 mL, 100 mL and 150 mL) amended with poultry litters, cow dung and a mixture of both amendments. The microbiological properties-and the total petroleum hydrocarbon content was analyzed for a period of six months using the pour plate techniques and Gas Chromatography (GC-FID), respectively. Agarose gel electrophoresis was used for plasmid detection. Mean total heterotrophic bacterial counts ranged between 40.5±0.5 x104 cfu-1 and 102.0 ±4.0 x104 cfu-1, for C1 (soil with poultry litter and cow dung with 50mL diesel) and Control 2. The mean total hydrocarbonoclastic bacterial counts ranged from 42.0±2.0 x104 cfu-1 to 66.5±2.5 x104 cfu-1 for B1 (soil with cow dung with 50mL diesel) and C3 (soil with poultry litter and cow dung with 150mL diesel). Bacillus subtilis (25.7%) and Staphylococcus aureus (4.73%) were reported as the isolates with the highest and least percentage frequency of occurrence. The percentage of diesel oil degradation was highest in C1 (98.5%) and lowest in Control 1 (31.6%). Plasmid extraction studies carried revealed that two out of the five hydrocarbonoclastic bacteria had both plasmids and chromosomal genes. The result has indicated the enhanced capacity of mixed amendments relative to individual waste treatment used in this study and should be recommended for bioremediation application.